2022
DOI: 10.3390/ma15155184
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Annealing and Thickness of Co60Fe20Yb20 Nanofilms on Their Structure, Magnetic Properties, Electrical Efficiency, and Nanomechanical Characteristics

Abstract: X-ray diffraction (XRD) analysis showed that metal oxide peaks appear at 2θ = 47.7°, 54.5°, and 56.3°, corresponding to Yb2O3 (440), Co2O3 (422), and Co2O3 (511). It was found that oxide formation plays an important role in magnetic, electrical, and surface energy. For magnetic and electrical measurements, the highest alternating current magnetic susceptibility (χac) and the lowest resistivity (×10−2 Ω·cm) were 0.213 and 0.42, respectively, and at 50 nm, it annealed at 300 °C due to weak oxide formation. For m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Conversely, rougher surfaces exhibit higher carrier conductivity, leading to a reduction in electrical resistance. The comparison with other designated materials can be seen in Table 1, including Cobalt Iron Ytterbium (CoFeYb) and Cobalt Iron Yttrium (CoFeY), deposited on Si(100) substrates [55,56]. The information presented in Table 1 highlights that the maximum χac in the current research is lower than observed in Co60Fe20Yb20 and Co60Fe20Y20 materials.…”
Section: Characterization Of Surface Roughnessmentioning
confidence: 74%
“…Conversely, rougher surfaces exhibit higher carrier conductivity, leading to a reduction in electrical resistance. The comparison with other designated materials can be seen in Table 1, including Cobalt Iron Ytterbium (CoFeYb) and Cobalt Iron Yttrium (CoFeY), deposited on Si(100) substrates [55,56]. The information presented in Table 1 highlights that the maximum χac in the current research is lower than observed in Co60Fe20Yb20 and Co60Fe20Y20 materials.…”
Section: Characterization Of Surface Roughnessmentioning
confidence: 74%